Challenges Faced by Family Caregivers of Individuals Living with Dementia in Japan During the COVID-19 Pandemic. - Tsuyuki, Toshiko; Asai, Takeshi; Kurosaki, Erina; Nakamura, Atsushi; Kishi, Kaori; Takeda, Fumi (Nursing Reports, 2024)
Background/Objectives: This study investigates the challenges faced by family caregivers of individuals with dementia in Japan, particularly in the context of the COVID-19 pandemic. Methods: We conducted a cross-sectional survey of 500 family caregivers of patients with dementia. Results: 56.4% of caregivers reported an increased caregiving burden, primarily due to extended caregiving hours, reduced access to public services, and restrictions on social interactions. This study found a strong preference for formal support, with 75.4% of caregivers desiring access to more comprehensive services. However, 19.4% of dementia patients were not utilizing any public services, largely due to a mismatch between available services and caregivers' actual needs, as well as societal resistance to inviting formal support into the home. Informal support systems, such as dementia family groups and cafes, were well-known, but participation rates remained low (5.4% and 5.8%, respectively), despite the potential benefits for reducing stress and providing emotional support. Key barriers included privacy concerns, reluctance to engage, and logistical challenges such as inconvenient access and time constraints. Conclusions: To mitigate the above challenges, this study recommends expanding telemedicine and remote support services, improving awareness of available resources, and offering flexible, tailored solutions to meet diverse caregiving needs. Additionally, increasing financial support, enhancing public recognition of caregiver roles, and providing psychological counseling and stress management programs are essential to alleviating both the emotional and economic burdens placed on family caregivers during the pandemic.